A low-riding patella in posterior stabilised total knee replacements alters quadriceps' mechanical advantage, resulting in reduced knee flexion moments. - Ward, T; Pandit, H; Hollinghurst, D; Zavatsky, A; Gill, H; Thomas, N; Murray, D (2012)
Abnormal in vivo Total Knee Replacement (TKR) kinetics is influenced by a range of factors, particularly by changes to the knee's geometric parameters such as the patellar tendon moment arm (PTMA). In this study, ground reaction force (GRF) measurements were combined with simultaneous fluoroscopic image measurements to investigate the relationship between abnormal TKR kinetics and geometric parameters. Nine Scorpio Cruciate Retaining (CR) TKR (Stryker, Newbury, UK), nine Scorpio Posterior Stabilized (PS) TKR and seven normal subjects performed a step-up activity on a forceplate in view of a fluoroscope. The TKR subjects were part of a larger ongoing randomised controlled trial. The maximum external knee flexion moment was 22.0% lower in the Scorpio PS group compared to the Scorpio CR group. No significant differences in PTMA were found between the groups. The Scorpio PS had a low-riding patella, with a 30.7% reduction in patellar height compared to the Scorpio CR. This was probably due to using a thick tibial insert after PCL release in the PS, and led to an 8° increase in patellar flexion angle which altered the patellar mechanism and reduced quadriceps' mechanical advantage. Consequently, PS subjects stepped-up more cautiously with a reduced knee flexion moment.